Factors, Causes and Outcomes of Consumers’ Decision to Buy Products via Facebook Live after the COVID-19 in Bangkok and Its Vicinity - Tawilprawat, Sikarin; muangjaroen, jaruwan (Journal of Applied Economics and Management Strategy, 2023)
The research’s objectives were: 1) to study consumer’s buying behaviour of products made through Facebook Live in Bangkok and its vicinity after the Covid-19, and 2) to study factors affecting consumers’ decision to buy products through Facebook Live after the Covid-19 in Bangkok and its vicinity. The sample for research was 390 consumers living in the Bangkok Metropolitan Region. The statistics used for data research were frequency, percentage, mean, standard deviation, and logistics regression analysis. The research found that the logistic regression model can predict an overall accuracy of 93.60 percent. Factors affecting consumers’ decision to buy products through Facebook Live after the COVID-19 in Bangkok and its vicinity. These factors are as follows: 1) Product aspects: The products have high quality and meet standards with complete and accurate details as advertised, 2) Emotional aspects: Consumers can access and immediately appreciate the products as well as entertainment value and influence from product reviewers, and 3) Behavioral aspects: Consumers can express their opinions, participate in interactive activities and can learn and explore diverse product information, making purchasing decisions easier. Based on this research, business operators can utilize online marketing components to develop marketing strategies suitable for their target audience, thereby increasing opportunities for business growth from both existing and new customers.